2013
DOI: 10.1111/bph.12224
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NF‐κB after chronic ethanol intake and haemorrhagic shock/resuscitation in mice

Abstract: BACKGROUND AND PURPOSEChronic ethanol abuse and haemorrhagic shock are major causes of global mortality and, separately, induce profound hepato-and immune-toxic effects via activation of NF-κB. Here, we assessed the effects of chronic ethanol intake upon the pathophysiological derangements after haemorrhagic shock with subsequent resuscitation (H/R), with particular attention to the contribution of NF-κB. EXPERIMENTAL APPROACHTransgenic NF-κB EGFP mice, expressing the enhanced green fluorescent protein (EGFP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Despite numerous reports on the deleterious effects of chronic or excessive alcohol abuse, others and our group have reported that moderate or acute use may exert beneficial effects (15)(16)(17)20,36). The negative effects of alcohol consumption have been linked to an increased inflammatory response, including increased cytokine release (14,15,37,38). Pro-inflammatory cytokines such as IL-1β, TNF, IL-6 and IL-8 have been identified as important contributors to the pathogenesis of organ damage, including lung as well as liver injury in models of acute inflammation (17)(18)(19)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous reports on the deleterious effects of chronic or excessive alcohol abuse, others and our group have reported that moderate or acute use may exert beneficial effects (15)(16)(17)20,36). The negative effects of alcohol consumption have been linked to an increased inflammatory response, including increased cytokine release (14,15,37,38). Pro-inflammatory cytokines such as IL-1β, TNF, IL-6 and IL-8 have been identified as important contributors to the pathogenesis of organ damage, including lung as well as liver injury in models of acute inflammation (17)(18)(19)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Control pair-fed animals received the equal amount of maltodextrin-supplemented diet (ctrl), in order to warrantee the isocaloric feeding. In alcohol-fed animals, the diet protocol consisted of a gradual increase in the EtOH dose in the liquid diet, beginning with 1.75% (v/v) for 5 days, and increasing to 2.63%, 3.50%, 4.38%, and 6.3% (v/v) as described before[ 20 , 25 ]. After 4 weeks of feeding, animals were weighted and allocated to hemorrhage and subsequent resuscitation group (H/R) or the control (sham) group[ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Numerous harmful pathophysiological changes directly affecting the liver, including steatosis, steatohepatitis, fibrosis or cirrhosis, are closely associated with the chronic ethanol intoxication[ 19 ]. These changes occurring in the setting of chronic ethanol-use cause an increased susceptibility to H/R-induced liver injury[ 20 , 21 ]. The underlying mechanisms involve at least in part increased NF-κB activation resulting in enhanced production of local proinflammatory cytokines, including IL-6 and increased infiltration of the liver with neutrophils, resulting in organ damage[ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-κB, however, is involved in the control of the transcription of many genes whose functions extend beyond the immune response, but are involved in more general stress responses [ 17 ]. Various physiological stress conditions such as liver regeneration and hemorrhagic shock can activate NF-κB [ 18 , 19 ]. Also physical stress, in the form of irradiation as well as oxidative stress to cells, induces NF-κB, that in turn activates a large variety of stress response genes [ 20 ].…”
Section: Introductionmentioning
confidence: 99%